Validation of the “sladecom” model as a contemporary panacea for the improvement of formal land market in Nigeria - Akinbola, Kazeem Bolayemi; Md Yassin, Azlina; Wan Yusoff, Wan Zahari (Open Access Publishing Group, 2017)
Land has been variously acknowledged as a perennial harbinger of socio-economic power that exudes prestige and class. It is the foundation for food and shelter, driving the very bedrock that significantly provides for most employment opportunities in the country side. Regrettably, as global urbanisation trends soars uncontrollably, land is rapidly becoming increasingly scarce assets in cities. Therefore, supplying of and demand for lands, especially within urban spheres, are though unfortunately never at equilibrium, but the present scenarios in formal window of urban land market, which is solely responsible for the supply of formal land for various developmental purposes, has been very unimpressive. This simply, has rendered delivery to be at its lowest ebb, such that accessibility, which is the measure of demand coefficients from the part of the various land users, to be hampered, the resultant effects of which is consistent decrease of the real estate stock. Hence, it is in astounding recognition of the above ugly scenario that this study was conducted, primarily to validate the potentialities of SLADECOM model which is an end product of a doctoral research. Essentially, this model is meant to remove all the established barriers that are rendering the supply side (i.e delivery) as well as the demand side (i.e accessibility) of the formal market for urban lands, so sub-optimal. Moreover, the following constructs and variables that survived the statistical screening exercise were coined as components of this Sladecom model for empirical validation, such as: structural and culturo-behavioural dynamics (scbd), socio-political and economic dictates (sped), human techno-analytical arsenals (htaa), policy relevance and appropriateness (pra), contents and context of policies (ccp) and role mediation regime (rmr).Furthermore, validation, which is unlike just any other survey, requires high level of integrity, as results from it are almost laws in their plausibility, which simply suggests that respondents with huge experience, towering knowledge and consummate understanding of the issues involved in the subject matter are carefully selected for data collection. Out of the rough total of over 500 individuals considered as the total population for the sample space, 205 individuals qualified for the sample frame, from which the sample size of 120 was chosen, upon which the structured questionnaires were distributed. Therefore, after necessary integrity checks, 92 out 107 questionnaires that were retrieved, were found to be valid, thus formed the denominator for the analyses, using 5 point Likert scale of measurement, corroborated with pie-charts for stronger inferential and descriptive statistical results and explanations. The findings amongst other things are that this model has great potential to drastically reduce multiple roles partitioning among formal land administration machineries and thus increases the speed, quality and quantity of service delivery to prospective teeming land users. Among the recommendations is that decisive actions must be expeditiously taken on generating more functional databases and also increase the frequency of contents updating of these databases. This will no doubt improve the technical prowess of formal land administration machineries, with resultant capability to address myriad of challenges of formal land delivery and accessibility in Nigeria.